Global TEC maps based on GNNS data: 2. Model evaluation. Issue 7 (24th July 2013) - Mukhtarov, P.; Pancheva, D.; Andonov, B.; Pashova, L.
Abstract: [1] The present paper presents a detailed statistical evaluation of the global empirical background TEC model built by using the CODE TEC data for full 13 years, 1999‐2011, and described in Part 1. It has been found that the empirical probability density distribution resembles more the Laplace than the Gaussian distribution. A further insight into the nature and sources of the model's error variable led up to building of a new error model. It has been constructed by using a similar approach to that of the background TEC model. The spatial‐temporal variability of the RMSE (root mean squares error) is presented as a multiplication of three separable functions which describe solar cycle, seasonal and LT dependences. The error model contains 486 constants that have been determined by least squares fitting techniques. The overall standard deviation of the predicted RMSE with respect to the empirical one is 0.7 TECU. The error model could offer a prediction approach on the basis of which the RMSE depending on the solar activity, season and LT is predicted. Key Points: Empirical probability density distribution resembles more Laplace distribution An error model is built RMSE depending on solar activity, season and LT can be predicted